Barriers to the implementation of artificial intelligence in small and medium-sized enterprises: Pilot study - Zavodna Lucie Sara; Überwimmer Margarethe; Frankus Elisabeth (Journal of Economics and Management)
Aim/purpose – This pilot study explores the main obstacles hindering the effective implementation of Artificial Intelligence (AI) in small and medium-sized companies (SMEs). By thoroughly understanding these barriers, organizations can develop customized strategies and interventions to overcome them, facilitating smoother and more successful AI adoption. The paper’s primary goal is to help organizations understand the barriers to AI adoption to develop tailored strategies and interventions to overcome these challenges, leading to a more efficient and successful integration of AI. Through a rigorous examination of real-world experiences and perceptions, this paper seeks to elucidate the multifaceted challenges that impede the effective deployment of AI solutions.